Life Cycle Cost (LCC) strategy and protocol on cost data input in Malaysia - Ayob, Mohd Fairullazi; Abdul Rashid, Khairuddin (2016)
There is a need to develop a clear procedure on the acquisition of cost data inputs of LCC and that procedure is best translated in the form of protocol. A protocol of LCC data input requirements process was developed, evaluated, validated and tested with a group of LCC experts through FGD approach to provide robust procedures on how the cost data could be made more available, accessible, current and reliable as inputs into the process of producing reliable LCC outputs in the Malaysian construction industry. The current findings can serve as a potential benchmark which could facilitate the clients, estimators and researchers in Malaysia and or in some other countries to calculate LCC better leading to better outputs